Pandemic Teaching: Exploration of Instructional Method Shifts - Leann M. R. Kaiser; Kelly McKenna; Diana Saade (Adult Education Research Conference, 2022)
COVID-19 forced educators to unexpectedly move to distance teaching, requiring a shift in instructional methods. This study examined practices instructors integrated into their online and face-to-face facilitation over the long term.
Keywords: Instructional methods; Online teaching; COVID-19 impacts; Higher education